Fear of breast cancer among young Spanish women: Factor structure and psychometric properties of the Champion breast cancer fear scale. - Aldo Aguirre-Camacho; Beatriz Hidalgo; Gustavo González-Cuevas (PLoS ONE)
Heightened fear of breast cancer (FBC) has been linked to increased distress following breast cancer diagnosis and to avoidance of mammography screening. To our knowledge, however, no studies have examined the nature of FBC exclusively among young females, even though they are overrepresented in media stories of breast cancer. Given that no instruments are available to assess FBC in the Spanish language, we sought to 1) evaluate the psychometric properties and factor structure of the Champion Breast Cancer Fear Scale (CBCFS), and 2) offer preliminary data on the nature of FBC among young women. Participants (N = 442, mean age = 21.17, range 17-35) completed the translated CBCFS (CBCFS-es) and the Spanish version of the Short Health Anxiety Inventory. The CBCFS-es demonstrated good concurrent validity, internal consistency, and test-retest reliability. Confirmatory factor analysis showed adequate fit to a one-factor solution. The majority of participants reported considerably high levels of FBC, as 25.34% and 59.73% of them scored above the moderate- and high-FBC cut-offs, respectively. Moreover, FBC could not be explained by general concerns regarding health and illness, given that levels of health anxiety were low. Implications for health education, research, and clinical practice are discussed.